OPTIMIZATIONS THE TENSILE-SHEAR STRENGTH OF TIG WELDING PARAMETERS FOR MILD STEEL AT DIFFERENT MATERIAL THICKNESSES - Dwicahyo, Tegar; Basit, Arul; Amar, Amar; Sukarman, Sukarman; Khoirudin, Khoirudin; Suhara, Ade (Jurnal Rekayasa Mesin, 2024)
This article presents a study on optimizing Tungsten Inert Gas (TIG) welding on mild steel (SPCC-SD/JIS G3141) with varying thicknesses of 0.6 mm and 0.8 mm. Automobile bodies commonly utilize mild steel with a material thickness ranging from 0.6 to 0.98 mm. The objective of this study was to ascertain the upper limit of tensile-shear strength that can be achieved by utilizing the specific parameters utilized in TIG welding. This study utilizes a three-level experiment and incorporates three input variables in the Taguchi experimental optimization method. The advantage of this approach lies in its ability to yield comprehensive outcomes while minimizing expenses, as it can be adapted to the resources available. An additional benefit is that this approach can be implemented in a multitude of industrial situations.The study's input variables are welding current, argon gas flow rate, and electrode diameter. Utilizing a continuous flow of argon gas of 12 LPM (liter per minute), a welding current of 55 A, and an electrode diameter of 1.6 mm, the maximum mean T-S strength of 3457.13 N was achieved. The ANOVA revealed that the flow rate, welding current, and electrode diameter had a per cent contribution of 50.07%, 26.89%, and 23.04%. The flow rate was the parameter with the most significant impact on the influential variable. The welding current and the electrode diameter do not significantly affect the response. The findings indicate that by adjusting the parameters to the optimal level determined by the Taguchi method, the S-N ratio for T-S strength increases by 9.30%, and T-S strength increases by 12.42%. The findings of this study offer a thorough comprehension of enhancing the TIG welding approach and can be further refined by incorporating additional variables.